Case of coexisting Nocardia cyriacigeorgica and Aspergillus fumigatus lung infection with metastatic disease of the central nervous system. Issue 3 (8th March 2022) - Roy, Moni; Lin, Rone-Chun; Farrell, John Joseph
Abstract : Nocardiosis is a rare opportunistic gram-positive bacterial infection. The genus Nocardia consists of non-motile, aerobic, non-spore-forming, catalase-positive, filamentous-branching bacteria with fragmentation into coccoid or bacillary forms. Opportunistic infections due to Nocardia are reported in immunocompromised patients. Aspergillus fumigatus is a conidia forming fungus that can be found in soil, plant matter and dust, causing invasive pulmonary and disseminated infection in immunocompromised patients. Both Nocardia cyriacigeorgica and A. fumigatus are known to cause pulmonary infection with metastatic dissemination to the central nervous system. We present a case of Nocardia and Aspergillus co-infection in a patient who presented within a few days of initiation of immunosuppressants for suspected systemic lupus erythematosus.